Would the Singaporean Approach to Whistleblower Protection Laws Work in Australia? - John McLaren; Wesley Kendall; Laura Rook (Australasian Accounting, Business and Finance Journal, 2019)
Federal, State and Territory Governments have enacted a range of statutory laws to protect whistleblowers. The aim of these laws is to provide protection to those individuals in the private and public sector who report unlawful acts made by organizations, contractors and their employees. Provided the disclosure is made in ‘good faith’, the person making the disclosure is afforded protection from being sued for defamation, breach of confidence under their employment contract or for breach of their common law fiduciary duty. This paper has two purposes; first, the objective of the Australian Government in introducing new whistleblowing laws that extend protection to the consumer protection area and taxation, namely the Treasury Laws Amendment (Whistleblowers) Bill 2017 - Exposure Draft is examined. Secondly, an alternative approach to whistleblowing is considered. By way of contrast, a Singaporean approach which heavily relies on self-reporting and an internal investigation involving an Audit Committee of the corporation is critically examined to assess the potential for introducing a self-reporting approach in Australia. Our analysis finds that in Singapore, culture plays a role in the attitude of the Singaporean employee contemplating reporting unlawful activity and, more importantly in how the disclosure is treated by the corporation or public institution. This paper adds to the literature which examines alternative approaches and attitudes to whistleblowing by providing a comparative discussion of the Australian and Singaporean legal approaches.
Keywords: Whistleblower laws; Singapore; Australia; Culture; Confucian values.